Pemanfaatan Media Lagu â€œHindia: Membasuhâ€ dalam Meningkatkan Keterampilan Menulis Puisi Kelas X di SMKN 1 Rawamerta - Dellaviane Syarafina; Sutri Sutri; Een Nurhasanah (Aksara: Jurnal Bahasa dan Sastra, 2023)
This study aims to determine the effect of using the media song "Membasuh" by the Indies in improving the poetry writing skills of class X at SMKN 1 Rawamerta. The research method used in this study is a quantitative method with an experimental design involving two classes; experimental class and control class. This research was conducted at SMKN 1 Rawamerta by taking two classes as samples, namely class X TKJ 1 with a total of 36 students and X TO 2 with a total of 34 students. Researchers obtain data by conducting pre-test/pretest and final testposttest on both samples. Data collection begins withpretest, then do the treatment/treatment, and the last one didposttest. Data acquisition and analysis results show that there is a significant difference between the experimental class that uses song media and the control class that does conventional learning. These results can be proven in non-parametric testsMann-Whitney with Asymp results. sig. 0.00 0.05 which proves that there is a significant difference between the experimental class and the control class. The effectiveness of learning is proven by testingN-Gain Score on both samples. The calculation results prove that learning in the experimental class is more effective with an acquisition of 57.10% in the category of quite effective, compared to learning that is applied to the control class with an acquisition of 17.51% in the category of ineffective.Keywords: Utilization of Song, Song Media, Poetry Writing Skills